(untitled) (Latakia University Journal -Engineering Sciences Series, 2017)
تعد المياه الجوفية مصدر هام لمياه الشرب ولذلك يعد تلوث المياه الجوفية مصدر قلق مستمر. فتلوث المياه الجوفية بعكس المياه السطحية يصعب تحديده والأصعب التحكم به ومعالجته، وقد يستمر لسنوات أو عقود. إن منطقة نبع ديفة في اللاذقية منطقة زراعية تعاني من مشاكل بيئية عديدة، ومن هنا تأتي أهمية تقييم قابلية نبع ديفة للتلوث باستخدام طريقة DRASTIC، ووضع خريطة قابلية المياه الجوفية للتلوث باستخدام GIS. بينت خريطة قابلية المياه الجوفية للتلوث أن معظم المياه المغذية لنبع ديفة لديها قابلية عالية ومعتدلة للتلوث. قدرت مساحة المنطقة التي مياهها الجوفية ذات قابلية مرتفعة للتلوث بحوالي ((82 Km2، أي تشكل حوالي (%48) من المساحة الكلية لمنطقة الدراسة التي تبلغ ((170 Km2. أما مساحة المنطقة ذات المياه الجوفية المعتدلة القابلية للتلوث بحوالي ((40 Km2، أي تشكل حوالي (%23) من المساحة الكلية لمنطقة الدراسة. وبالتالي لابد من اتخاذ إجراءات كفيلة لحماية المياه من التلوث وذلك من خلال الإدارة المتكاملة لموارد المياه الجوفية. Groundwater is an important source of drinking water. Therefore; groundwater contamination is a source of continuing concern. Groundwater contamination is unlike surface water contamination, because it is difficult to define and harder to be controlled and treated. It may also last for years or decades. Deveh Spring area is an agricultural area in Lattakia. It suffers from many environmental problems, so, it is very important to assess spring water vulnerability using DRASTIC and create water vulnerability assessment map by GIS. The map showed that the recharge water to Deveh Spring has a high and moderate vulnerability to contamination. The area of high vulnerable groundwater zone is (82Km2), which is about (48%) from the whole study area. The area of moderate vulnerable groundwater zone is (40Km2), which is about (23%) from the whole study area. Sufficient actions must be taken to protect water from contamination, through the integrated management of groundwater resources.